Interpretasi profil Minat peserta didik ditinjau dari kemampuan kognitif matematika pasca pandemi Covid-19 - Wira Novantri; Amalia Rizky; Novita Anggraini Putri; Nidaul Himmah; Nicky Ria Azizman (Eksponen, 2023)
This study aims to analyze students' interest in learning from the cognitive abilities of class VII SMPN 19 Jambi City. This research is a qualitative descriptive research, with a case study approach. The subjects in this study were 6 class VII students of SMP N 25 Jambi City. The research instrument used was a question of students' cognitive tests on ratio material and a questionnaire on students' interest in learning mathematics. Questionnaire distributed via google form. After the researcher carried out the test, then 6 subjects were selected to be the focus of this study who would later be interviewed. The data obtained from the students' cognitive ability tests will be used in the analysis of the learning interests of students who have high, medium or low abilities. The results of the study show that students' excellence in learning in terms of numeracy skills is regulated based on the acquisition of scores in doing skills tests, completing interest in learning, and interviews, indicating that students' excellence in learning science is in the lower grades. This is consistent with in-depth interviews with six subjects representing high, medium and low ability categories. Subjects S1 and S2 are in the high class seen from the acquisition of scores on the cognitive ability test, and are in a very high classification seen from the results obtained from the interest in learning questionnaire. This was reinforced by in-depth interviews, it was found that S1 and S2 subjects really liked learning mathematics, easily understood math material and continued to be actively involved during learning. Keywords: Student’s interest, cognitive abilities, learning mathematics